Factors affecting to managerial success of an inter-organizational strategic relationship - Heimonen, Jesse (My University, 2013)
As the technological development and the change of the business environment are faster than ever, sustainable competitive advantage has become increasingly challenging to attain. To foster competitiveness many companies have formed strategic alliances. However, gaining expected value from the relationship has proved to be difficult. The issue appears to be in attaining the value rather than lacking the potential value. Hence, the motivation for this thesis and the primary objective of this study is to identify some of the key factors that influence the managerial success of an inter-organizational strategic relationship. To provide a solid picture of the factors affecting the managerial success of an inter-organizational strategic relationship there are three key theoretical areas that this thesis examines. Firstly, it appears to be important to understand why companies prefer collaboration in areas requiring knowledge exchange, secondly to identify the factors affecting the inter-organizational knowledge exchange, and thirdly to establish how such relationships can be managed. Hence, the literature part of this thesis examines the latest articles published in top management and strategic management journals regarding these three key theoretical areas. In addition, to support the creation of a holistic picture, the thesis introduces findings of a qualitative empirical study from the Finnish technology industry. The findings of the study suggest that there are at least five themes that are important for the success of a strategic relationship: 1.) Existence of a market need; 2.) Realistic ability to fulfill the need together; 3.) Willingness and commitment; 4.) Capability to implement the jointly agreed strategy; 5.) Continuous two way communication at all hierarchical levels.
Keywords: Strategic Management; Knowledge Exchange; Vertical Relationship; Resource-Based View; Buyer-Supplier Relationship; fi=Johtaminen ja organisaatiot|en=Management and Organization|